Sex Differences in Mortality After CABG Surgery - Figueiredo Neto,José Albuquerque de (2015)
ABSTRACT INTRODUCTION: Numerous studies have shown that women undergoing coronary artery bypass graft surgery present higher mortality rate during hospitalization, and often complications when compared to men. OBJECTIVE: To compare the mortality of men and women undergoing coronary artery bypass graft surgery and identify factors related to differences occasionally found. METHODS: Retrospective cohort study conducted with 215 consecutive patients who underwent coronary bypass surgery. RESULTS: Women had a higher average age. Low body surface and dyslipidemia were more prevalent in women (1.65 vs . 1.85, P<0.001: 53% vs . 30%, P =0.001), whereas history of smoking and previous myocardial infarction were more prevalent in men (35% vs .14.7%, P =0.001; 20% vs . 2.7%, P =0.007). Regarding complications in the postoperative period, there was a higher rate of blood transfusions in women. The overall mortality rate was 5.6%, however there was no statistically significant difference in mortality between men and women. It was observed that among the patients who died, the average body surface area was lower than that of patients who did not have this complication. CONCLUSION: There was no difference in mortality between the sexes after coronary artery bypass graft in this service.